2012
DOI: 10.1177/0022034512438401
|View full text |Cite
|
Sign up to set email alerts
|

Spry1 and Spry2 Are Essential for Development of the Temporomandibular Joint

Abstract: The temporomandibular joint (TMJ) is a specialized synovial joint essential for the function of the mammalian jaw. The main components of the TMJ are the mandibular condyle, the glenoid fossa of the temporal bone, and a fibrocartilagenous disc interposed between them. The genetic program for the development of the TMJ remains poorly understood. Here we show the crucial role of sprouty ( Spry) genes in TMJ development. Sprouty genes encode intracellular inhibitors of receptor tyrosine kinase (RTK) signaling pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
39
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 31 publications
2
39
0
Order By: Relevance
“…This is consistent with our previous report of the requirement of Spry1 and Spry2 in proper formation of the temporomandibular joint (24). The loss of Spry2 expression does not affect the initiation of chondrogenesis, as limbs of Spry2 −/− mice appear to develop normally until late gestation.…”
Section: Discussionsupporting
confidence: 94%
“…This is consistent with our previous report of the requirement of Spry1 and Spry2 in proper formation of the temporomandibular joint (24). The loss of Spry2 expression does not affect the initiation of chondrogenesis, as limbs of Spry2 −/− mice appear to develop normally until late gestation.…”
Section: Discussionsupporting
confidence: 94%
“…Whereas the blastemal formation of these two major components of the TMJ occurs independently, the presence of the condyle is required for the sustained development of the glenoid fossa (Wang et al 2011; Gu et al 2014). However, the TMJ condyle and disc can develop in the absence of the glenoid fossa (Purcell et al 2012). Although previous studies of TMJ development have been largely focused on the condyle and the articular disc, developmental defects in the glenoid fossa have been reported only in a few genetically modified mouse models (Wang et al 2011; Purcell et al 2012; Gu et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…A number of transcription factors and growth factors have been reported with regard to their essential roles in TMJ morphogenesis and growth, such as Runx2, Sox9, Shox2, Spry1 and Spry2, Bmpr1A, Tgfbr2, and Ndst1 (Shibata et al 2004; Fukuoka et al 2007; Mori-Akiyama et al 2003; Wang et al 2011; Gu et al 2008, 2014; Li et al 2014; Purcell et al 2012; Oka et al 2007; Yasuda et al 2010). Among them, Indian hedgehog (Ihh), a signaling molecule that plays a pivotal role in the regulation of chondrocyte proliferation, maturation, and ossification both in long-bone development and digit joint formation (St-Jacques et al 1999), has also been found to be essential for TMJ development (Shibukawa et al 2007; Purcell et al 2009; Gu et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Sprouty1 has been suggested as a candidate tumor-suppressor in medullary thyroid carcinoma [36]. In addition, Sprouty1 also has essential cellular roles in neural and endothelial differentiation of mouse embryonic stem cells [37] and normal development of the temporomandibular joint [38]. Despite the very important role of Sprouty1 in cellular function, no mutations or associations in the SPRY1 gene have been reported.…”
Section: Discussionmentioning
confidence: 99%